1994
DOI: 10.1093/nar/22.6.1059
|View full text |Cite
|
Sign up to set email alerts
|

The hnRNP F protein: unique primary structure, nucleic acid-binding properties, and subcellular localization

Abstract: More than 20 different heterogeneous nuclear ribonucleoproteins (hnRNPs) are associated with premRNAs in the nucleus of mammalian cells and these proteins appear to influence pre-mRNA processing and other aspects of mRNA metabolism and transport. The arrangement of hnRNP proteins on pre-mRNAs is likely to be unique for each RNA and may be determined by the different RNA-binding preferences of each of these proteins. hnRNP F (Mr = 53 kD, pi = 6.1) and hnRNP H (Mr = 56 kD, pl = 6.7-7.1) are abundant components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
147
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 60 publications
10
147
0
1
Order By: Relevance
“…Searches for proteins with identity to the found sequences were performed as described in Materials and Methods, using available public databases. Proteins showing the highest identities are listed in Table 1 [23,[27][28][29]. The sequence (HTGPNSPDTA) was 100% identical to sequences in human hnRNP H, hnRNP H' and ORF-FTP-3.…”
Section: Sequence Analysis Of the Common Nuclear-matrix Proteinsmentioning
confidence: 99%
“…Searches for proteins with identity to the found sequences were performed as described in Materials and Methods, using available public databases. Proteins showing the highest identities are listed in Table 1 [23,[27][28][29]. The sequence (HTGPNSPDTA) was 100% identical to sequences in human hnRNP H, hnRNP H' and ORF-FTP-3.…”
Section: Sequence Analysis Of the Common Nuclear-matrix Proteinsmentioning
confidence: 99%
“…This protein tends to form a heterodimer with hnRNP F and shows preference for G-rich tracts of RNA. 2,[6][7][8] It has also been shown that hnRNP H1 interacts with the DGCR8 complex and facilitates microRNA processing in HeLa cells. 9 The impact of hnRNP H1 binding on alternative splicing has been associated with several diseases, such as cystic fibrosis, 10 congenital myasthemic syndrome, 11 and amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%
“…G-tracts are also abundant downstream of mammalian polyadenylation signals 7 and in 5' and 3' untranslated regions (UTR) 8 . Some of the trans-acting factors that bind to these G-tracts belong to the heterogeneous nuclear ribonucleoprotein (hnRNP) F/H family of proteins that consists of five members (hnRNP F, hnRNP H, hnRNP H', hnRNP 2H9, and GRich Sequence Factor (GRSF) 1) 9,10 . GRSF-1 is mainly involved in translation regulation 11,12 and Internal Ribosome Entry Site (IRES) mediated translation 13 , while hnRNP H, H' and F are mostly involved in the regulation of alternative splicing [14][15][16][17][18][19][20][21][22][23] and polyadenylation [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are very similar in sequence (hnRNP F and H share 78% sequence identity) 10,41 . The RNA binding domains of hnRNP F/H proteins were denoted qRRMs because of their similarity to the classical RRM motif.…”
Section: Introductionmentioning
confidence: 99%